If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x/3)+2=-1
We simplify the equation to the form, which is simple to understand
(x/3)+2=-1
Simplifying:
( + 0.333333333333x)+2=-1
Remove unnecessary parentheses
+ 0.333333333333x+2=-1
We move all terms containing x to the left and all other terms to the right.
+ 0.333333333333x=-1-2
We simplify left and right side of the equation.
+ 0.333333333333x=-3
We divide both sides of the equation by 0.333333333333 to get x.
x=-9
| 1+4x=1+2(2-3x) | | (x/2)+7=10 | | 3xy+x= | | 14y-2-10y=48 | | 5(6n-5)+5=4(2n+10)+7n | | (5x^2+32x)/x | | 3(2x+5)=29 | | 18x/81 | | ax+c=z+b | | (x/2)+3=0 | | (x/2)+1=0 | | 4(m-1)-10m=-10(m+4) | | (x/3)+1=2 | | 4[x-(-7)]=2(x+8) | | 2x-6+14=38 | | (3x-4)(5/x-1/2)=0 | | (2-2i)(9-3i)= | | 5x-1=37 | | x(2x)=49 | | 15/5w | | 5w/15 | | ax-2b=3b | | -17=(-2)(2)+b | | 60+2x+10= | | 72x^2-59x+12=0 | | 6-2(4x+1)=16 | | (8x/9)+(-2)=6 | | 6(6-6)=4x+4 | | 2x^2+7x-3=8+x | | (x/3)+1=4 | | 72.5=3.5x-6 | | (x/5)-3=-5 |